Documentation of folk-medicinal uses of fruit tree species by the indigenous communities of Sikkim Himalayas - Sudip Kumar Dutta; Prakash Chettri; VK Mishra (Phytomedicine Plus)
Background: Sikkim is one of the Himalayan states in India and the only fully organic state in the country. Despite being a hotspot for biodiversity worldwide, it has received comparatively limited research. Indigenous people of the state place a great value on the edible wild fruit plants, which are also a significant source of ethnomedicine. Aim: The aim of the current study, conducted from 2021 to 2024, was to document the wild edible fruits of the Indian state of Sikkim and their socioeconomic significance among rural communities, as well as their ethnomedical uses. Methods: A total of 76 people from 23 villages, spanning a range of age groups (45–75 years), with both male and female respondents, were interviewed. Results: There were a total of 59 fruit species found, representing 48 genera and 32 families. Numerous illnesses, including stomach issues (dysentery, diarrhea, ulcers, vomiting, and constipation), fever, bronchitis, diabetes, jaundice, toothaches, anemia, swellings, skin conditions, bone fractures, itching, conjunctivitis, viral diseases, urinary diseases, tuberculosis, heart conditions, and many more, can be cured by these wild edible fruits that grow locally. Numerous other researchers worldwide, and in the northeastern Himalayan region specifically, have reported similar findings. Among all the families, Rosaceae accounted for the maximum with a total of 14 % of total of genera, followed by Moraceae (12 %), Rutaceae (8 %), Anacardiaceae (7 %), Combretaceae (5 %) and Elaeagenaceae, Fabaceae, Lauraceae, Myrtaceae, Rubiaceae (3 % each). In terms of the fruits' socioeconomic value, the majority of wild fruits are used in rural areas for traditional medicine, firewood, house construction, animal feed, and charcoal. The majority of these fruits can be purchased in the neighborhood market for between Rs. 60 and Rs. 300 per kilogram. Conclusions: It is recommended that the great variety of edible wild fruit plants be preserved for use in the future. Certain species can be cultivated on marginal soils with little agricultural value and in conventional agroforestry systems. Despite their many applications, these fruits have not yet received adequate documentation. Therefore, it is crucial to record these priceless species before they go extinct.